Crowding Out Effect of Public Borrowing: The Case of Jordan - Al-Majali, Ahmad A. (International Review of Management and Marketing, 2018)
This study aims to investigate the effect of government borrowing (Net claim no government) from Jordanian banks on Credit Facilities Extended by Licensed Banks to Private Sector. A Vector error correction model (VECM) is used to investigate the relationship between public borrowing and private credit. The paper concludes that government borrowing from the domestic banks leads to a more than one to one crowding out of private credit. This effect implies that government borrow from banks is not the only reason behind crowding out private credit. The increase in banks' treasury bills and bonds also reflects banks' preference to invest excess liquidity in a low risk high return investment. This is a case where the banking sector is colonized by "lazy banks". Keywords: Credit Facilities to Private Sector, Net claim no government, Banking Sector, and Crowding Out effect. JEL Classifications: E5, G2